Analysis of the Use of Constructive Journalism in the News 'Police Shoot Police' in the Online Media Tirto.id: Analisis Penggunaan Jurnalisme Konstruktif dalam Berita 'Polisi Tembak Polisi' di Media Online Tirto.id - Qorib, Fathul; Kristie, Erasa; Hakim, Lukman (Kanal: Jurnal Ilmu Komunikasi, 2024)
The coverage of the "police shooting police" case in Indonesia has been in the public spotlight and has led to various perspectives in the mass media. Tirto.id media, as one of the leading news platforms, seeks to apply the concept of constructive journalism in its reporting. This study aims to determine the extent to which Tirto.id implements the elements of constructive journalism in the news related to the case. This research uses a descriptive qualitative approach to reveal the application of constructive journalism in the news of "police shooting police" in Tirto.id media. The objects of this research are 21 news articles published between July 11, 2022 and August 17, 2022. The constructive journalism theory used includes five elements: solutions, future orientation, depolarization, constructive interviewing, and Rosling. The results showed that out of 42 downloaded news articles, 21 analyzed news articles successfully applied at least two elements of constructive journalism. These news not only provided solutions, but also highlighted future orientation, reduced polarization, conducted constructive interviews, and used data to show progress in handling cases. The news presented by Tirto.id also accommodates the interests of the audience by emphasizing human rights and the law in favor of the shooting victim, Brigadier J. In conclusion, although Tirto.id has tried to implement constructive journalism, there is still room for improvement, especially in integrating all elements of constructive journalism in every news story.